"Treat everybody right": Examining foodways to improve food access - Alex Hill (Journal of Agriculture, Food Systems, and Community Development, 2021)
Detroit is regularly assumed to be a “food desert” despite contradicting evidence. With fruits and vegetables available at each of Detroit’s 70 independent, full-line grocery stores, there remains a lack of understanding among media and academics of residents’ perception and preferences for food access. A baseline study was initiated during the summer of 2014 to understand residents’ own perceptions of food access and to assess the socio-cultural foodways utilized by residents. A total of 207 Detroit residents participated in focus groups and interviews to discuss food provisioning. Residents identified a wide range of food access points, from home gardens and fishing to specialty meat markets and big-box stores. However, 60% of residents reported that their primary grocery store was a chain supermarket outside the city limits. Residents highlighted “customer service” and in-store treatment as key factors in choosing where to shop for food. These new findings present contradictions to assumptions about food access in Detroit and similar cities. The findings point to a significant opportunity to leverage geo-ethnographic methods in order to focus on resident perceptions and preferences to improve food access.